2018
DOI: 10.1371/journal.pone.0198963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grain processing methods on the expression of genes involved in volatile fatty acid transport and pH regulation, and keratinization in rumen epithelium of beef cattle

Abstract: Two experiments were carried out to evaluate the effects of corn and sorghum with different processing methods on the expression of genes involved in volatile fatty acids transport and pH regulation, and ruminal keratinization in rumen epithelium of finishing bulls. For Exp. 1, five rumen cannulated Nellore bulls were used in a 5x5 Latin square arrangement, with 14 d for adaptation and 9 d for sample collection. Treatments were: dry ground corn, dry ground sorghum, reconstituted corn, reconstituted sorghum, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“… Tajima et al (2001) indicated that long-term feeding of high-concentrate diets decreased the acetate:propionate ratio in the rumen fluid whereas it increased the concentration of total VFA, suggesting that ruminal corneum exfoliation in HS cows may also be attributed to increased total rumen VFA concentration. In addition, the transport and absorption of VFA by the ruminal epithelium depend on the integrity of the corneum and the degree of keratinization ( Galfi et al, 1991 ; Del Bianco Benedeti et al, 2018 ). Yohe et al (2019) reported that the exfoliation of the corneum and the hyperkeratosis of the epithelium reduce the ability of the ruminal epithelium to transport and absorb VFA.…”
Section: Discussionmentioning
confidence: 99%
“… Tajima et al (2001) indicated that long-term feeding of high-concentrate diets decreased the acetate:propionate ratio in the rumen fluid whereas it increased the concentration of total VFA, suggesting that ruminal corneum exfoliation in HS cows may also be attributed to increased total rumen VFA concentration. In addition, the transport and absorption of VFA by the ruminal epithelium depend on the integrity of the corneum and the degree of keratinization ( Galfi et al, 1991 ; Del Bianco Benedeti et al, 2018 ). Yohe et al (2019) reported that the exfoliation of the corneum and the hyperkeratosis of the epithelium reduce the ability of the ruminal epithelium to transport and absorb VFA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on early weaning in ruminants have mainly focused on growth performance, blood physiological parameters, and rumen development ( Carroll et al, 2009 ; Schichowski et al, 2010 ; Knights et al, 2012 ; O’Loughlin et al, 2014 ; Lambertz et al, 2015 ; Ekiz et al, 2016 ; Liu et al, 2016 ); meanwhile, relatively little is known about the effect of early weaning on the intestinal barrier of ruminants. However, research does suggest that weaning stress has a remarkable effect on the intestinal barrier function of non-ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…Transporter genes (SLC family) are considered to be responsible for pH regulation by rumen epithelial absorption 10 . A low ruminal pH or high-grain diet enhances rumen epithelial absorption via enhanced transporter gene expression, such as monocarboxylate transporter (MCT1; 5), sodium hydrogen exchanger isoform 3 (NHE3 18 ;), and downregulated in adenoma (DRA 19 ;). In the present study, we observed the opposite, i.e., most of the 22 different SLC family genes identified were downregulated (11/13) during the first period and then upregulated (12/19) during the second period.…”
Section: Discussionmentioning
confidence: 99%